The Health Worker Motivation and Competence in the Utilization of MCH Handbook in Bireuen District - Yuliana Diah; Zulhaida Lubis; Sri Rahayu Sanusi (Britain International for Academic Research (BIAR) Publisher, 2020)
Book maternal and child health (MCH) is a program to improve the quality of health services for mothers and children in order to realize the degree of public health, This study aimed to analyze the motivation and competence of health personnel in the use KIA book in Bireuen district. This research method is qualitative phenomenological approach with a number of informants were 21 people including 4 coordinators KIA, 4 head of public health centers, 4 midwives village health centers, one business and one Kasie Nutrition district MCH / Nutrition. Data retrieval techniques such as interview, recording equipment, stationery, note in the field. The results of the research to get the motivation and competence of health personnel in the use KIA book and presents examples of how to use KIA book as the main media in promotive and preventive give effect to pregnant women and mothers in the use KIA book. The conclusion of this study is the motivation and competence of health personnel in the conduct promotive and preventive efforts on pregnant women and mothers through the use KIA book. This study will provide advice on how to increase the utilization of KIA book as a medium in promotive and preventive efforts for health workers to improve their knowledge and willingness of the community to improve community health status in Bireuen district.